Focussing attention on oneself increases the perception of being observed by others - Canvin, L; Janecka, M; Clark, D (Textrum, 2016)
Patients with Social Anxiety Disorder (SAD) often report elevated levels of self-focussed evaluative attention (SFEA), and seem excessively concerned with being observed by others. This study tested whether SFEA increases the perception of being observed by others. A sample of 52 high and 52 low socially anxious participants estimated the percentage of people ‘looking at you’ in several matrices of faces. A control task used matrices of clocks. SFEA was manipulated. As predicted, increasing SFEA led to significantly higher estimates of people ‘looking at you’ in both groups. Estimates on the control task were not affected by SFEA, thus the effects appear specific to social stimuli. These findings suggest that the increased levels of SFEA that characterise patients with SAD could contribute to their enhanced perception of being observed by others. The findings have implications for the role of attention training in the treatment of SAD.